The complete Peanuts, 1993-1994 - Schulz, Charles M. (Charles Monroe), 1922-2000 (Fantagraphic Books, 2014)
Collects all the "Peanuts" comic strips published in newspapers from 1993 to 1994, including both daily and Sunday strips.